P127Plakoglobin deficiency may predispose endurance-trained mice to atrial arrhythmias. (15th July 2014) - Syeda, F; Kemper, M; Vloumidi, E; Hopkins, S; Yu, TY; Riley, G; Kirchhof, P; Fabritz, L
Abstract: Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited disorder that causes sudden death in young athletes. Loss-of-function mutations of desmosomal proteins including plakoglobin are linked with ARVC and ventricular arrhythmias in trained mice. Intensive endurance training increases atrial arrhythmias in rats. We tested endurance-trained heterozygous plakoglobin deficient (Plako+/-) mice for atrial arrhythmia susceptibility. Methods: Plako+/- mice and WT littermates underwent group swim-training for total average swimming times of 50 hours over 8 weeks. Echocardiography was carried out before and after this period. Hearts were rapidly excised and perfused with Krebs solution and left atrial monophasic action potentials were recorded. Inter-atrial activation times (AT) and action potential durations (APDs) were measured during right atrial pacing at 100ms fixed-rate cycle lengths. An 8-pulse train followed by a single extrastimulus, was used to assess atrial arrhythmia inducibility. Results: Training increased left ventricular wall width (mm) by 13% in WT and Plako+/- mice (WT: 0.58±0.01 vs 0.66±0.01*; Plako+/-: 0.58±0.02 vs 0.66±0.01*). Right ventricular parameters e.g. RV diameter (mm) was increased after training, in Plako+/- (1.77±0.03) vs. WT (1.51±0.03)*. The number of hearts with induced atrial arrhythmias longer than 1sec, was greater in Plako+/- (6/13) than WT (0/8*; figure). AT, atrial weights, LA APD90 and refractoriness did not differ between genotypes. Hearts of trained Plako+/- mice were also more susceptible to induced ventricular arrhythmias than trained WT mice (WT: 1/12; Plako+/-: 7/15 hearts*). *p<0.05. Conclusion: Our findings suggest that defective cell-cell contact proteins predispose to training-induced atrial arrhythmias.